Financialization and generational differences in the correlates of perceived importance of investment in Hong Kong. Issue 2 (27th November 2019) - Lee, Francis; Tang, Gary; Tsang, Chung-Kin
Abstract : Purpose: The purpose of this study is to examine how people's perceptions of the importance of financial investment relate to their value orientation, societal perceptions and policy attitudes. Tying together insights from theoretical analysis of the financialization of society and Mannheim's (1972) theory of generation, this study hypothesizes that perceived importance of investment should be less connected to a desire for a wealthy lifestyle and more connected to a critique of social inequality among the young generation. Analysis of survey data ( N = 1, 020) from Hong Kong, an international financial hub, shows that perceived importance of investment relates positively to consumer materialism, perceptions of social inequality and support for social democratic policies. More importantly, the relationships between the latter variables and perceived importance of investment vary across age groups in ways largely consistent with the expectation. The findings illustrate the changing social significance of financial investment and the reluctant embracement of investment by young people. Design/methodology/approach: A representative telephone survey ( N = 1, 020) was conducted and analyzed. Findings: The analysis shows that perceived importance of investment relates positively to consumer materialism, perceptions of social inequality and support for social democratic policies. More importantly, the relationships between the latter variables and perceived importance of investment vary across age groups in ways largely consistent with the expectation. Originality/value: The findings illustrate the changing social significance of financial investment and the reluctant embracement of investment by the young generation. It is, to the authors' knowledge, the first study in Hong Kong addressing people's attitudes toward investment in relation to the notion of financialization.